ETMR-20. IMPACT OF HIGH DOSE CHEMOTHERAPY WITH AND WITHOUT METHOTREXATE (MTX) ON OUTCOME OF PATIENTS WITH EMBRYONAL TUMORS WITH MULTI-LAYERED ROSETTES (ETMRs): A REPORT FROM CHILDREN'S ONCOLOGY GROUP PHASE III TRIAL ACNS0334. (4th December 2020) - Mazewski, Claire; Kang, Guolian; Kellie, Stewart; Gossett, Jeffrey; Leary, Sarah; Li, Bryan; Aridgides, Paul; Hayes, Laura; Reddy, Alyssa; Shaw, Dennis; Burger, Peter; Judkins, Alexander; et al.
Abstract: Infant embryonal brain tumors comprise a spectrum of histologic and molecular entities including medulloblastoma (MB) and tumors collectively called CNS PNET's, including supratentorial PNET (sPNET), pineoblastoma and other less common histologic entities. Non-MB embryonal tumors, historically considered high risk disease, were included in ACNS0334, A Children's Oncology Group prospective phase III trial which compared efficacy of an induction regimen with and without methotrexate combined with high dose chemotherapy and stem cell rescue; no radiation was mandated. Molecular testing performed after ACNS0334 closure identified 14 patients with embryonal tumors with multi-layered rosettes (ETMRs), a new molecular entity previously classified under various diagnostic categories. ETMR patients made up 20% of the molecularly analyzed ACNS0334 cohort and were predominantly females. Tumors were largely non-metastatic (10/14 M0, 1 M1, 3 M2/M3) and originated in the cerebrum (8), cerebellum (3) and pineal gland (3). Gross total tumor resection was achieved in 5/11 patients with M0/M1 disease; 9/14 patients completed full treatment with 5 randomized to MTX induction and 9 to no-MTX. Five of 14 patients progressed on treatment, one had a toxic death. Disease progression was primarily local (88 %). No difference by methotrexate randomization was observed. Four patients are alive without progression 5–10+ years off therapy, none received radiation. No patients received radiation prior to progression. Four were irradiated after progression and died from disease within 3 to 13 months. Our study, a first report on ETMRs prospectively treated on a clinical trial, suggests high dose chemotherapy benefits a portion of ETMR patients.